The yellow-bellied sea snake, Hydrophis platurus (Squamata: Elapidae), off the Southwestern Pacific coast of Nicaragua, Central America - De-Weerdt, Joëlle (2021)
Introduction: The yellow-bellied sea snake (Hydrophis platurus, formerly Pelamis platurus) is known to occur along the Pacific coast of Central America. However, there are no marine records of this species off the coast of Nicaragua. Objective: Report the first in situ marine observations of the yellow-bellied sea snake observed on three occasions in 2020 during cetacean surveys off the southwestern Pacific coast of Nicaragua. Methods: During the sightings, photographs were taken which allowed the identification of the species based on morphology. Sea surface temperature, sea state, and distance to the coast are presented as descriptors of the habitat of the records. Results: Three field observations of yellow-bellied sea snakes were recorded on separate occasions. Sightings occurred within 30 km of each other and 3.3 km from the coast. Average sea surface temperature was 26.6 °C  with low swell and sea state. Conclusions: The present information offers new knowledge about the presence of the yellow-bellied sea snake on the Pacific coast of Central America, contributing to the biodiversity record in Nicaragua.